A simulation study of Io‐related Jovian decametric radiation: Control factor of occurrence probability. Issue 8 (27th August 2013) - Matsuda, K.; Katoh, Y.; Terada, N.; Misawa, H.
Abstract : [1] Io‐Jupiter interaction leads to auroral emissions and Jovian decametric radiations (Io‐DAM). The longitudinal distribution of the Io‐DAM occurrence probability has been considered to be controlled by the footprint magnetic intensity of each hemisphere. Recent observations revealed that the brightness of the main auroral spot is mainly modulated by Io's magnetic latitude. In the present study, we propose that the Io‐DAM occurrence probability is controlled by the north‐south asymmetry of the footprint magnetic intensity, in addition to Io's magnetic latitude. Hall magnetohydrodynamic equations are solved in the corotating meridional plane, which includes the Jovian ionosphere of finite thickness. We assume that the ionospheric Pedersen conductance is inversely proportional to the footprint magnetic intensity; the conductance is nearly the same for both ionospheres at a longitude of 290°, while twice higher for the south than for the north at a longitude of 110°. Above the northern ionosphere, the parallel current density further than 20° downstream of the main spot is estimated to be 1.5–2.0 times larger for 290° than for 110°. This indicates that if the Io‐DAM lead angle is large, the suppressed Io‐DAM occurrence probability for the northern hemisphere around 110° would be caused by the north‐south asymmetry of the footprint magnetic intensity. A large current density conducted into the south around 110° would be the source of the Io‐D component, radiated from the southern hemisphere. The observed brightness of the Io‐related auroras is discussed in the context of the intensity of the parallel current density. Key Points: Io‐Jupiter interaction is simulated in the corotating meridional plane. North‐south ratio of footprint magnetic intensity controls Io‐DAM occurrence. The origin of the Io‐DAM morphology is discussed.